In situ synchrotron X-ray diffraction of thin films under perturbation by an electric field. (10th December 2018) - Sønsteby, Henrik Hovde; Wind, Julia; Jensen, Martin; Aarflot Storaas, Thomas; Chernyshov, Dmitry; Fjellvåg, Helmer
Abstract: Piezo- and ferroelectric thin films attract a lot of attention due to their wide range of applications including microsensors, microactuators, memory devices and use in high frequency electrical components. For many of these applications, a fundamental understanding of crystal symmetry, lattice parameters and domain size and shape under perturbation by an electric field is crucial for design and device performance. In the current article, we show how the application range of a traditional large facility single crystal beam line can be extended to study piezo- and ferroelectric switching in thin films. In order to exemplify the power of this technique. We provide results from in situ diffraction studies of epitaxial films of Kx Na1-x NbO3 (100)ǁPt(111)@Si(100). Changes in lattice parameters and domain growth and switching can be probed rather straightforwardly. This results in a large array of coupled information on structure and electric properties that furthermore is important to design future high quality thin film devices.